Structural characterization of α, ω-DH6T monolayer films grown at the liquid–liquid interface. Issue 42 (14th October 2021) - Johnson, Manuel; Hawly, Tim; Wu, Mingjian; Spiecker, Erdmann; Fink, Rainer H.
Abstract : The molecular self-organization of alkyl-functionalized hexathiophene monolayers prepared at the solvent–water interface is investigated by complementary microscopy techniques. Abstract : The molecular self-organization of α, ω-dihexylsexithiophene (α, ω-DH6T) monolayers prepared at the solvent–water interface is investigated by complementary microscopy techniques. Our study focuses on the influence of solvents and initial droplet volume on the resulting film morphology. Long-range extended domains in the monolayer regime are detected by visible light microscopy only for toluene. Small-area electron diffraction (SAED) proves the formation of single-crystalline monolayers with structural parameters identical to the organic bulk crystals. In comparison with conventional vacuum sublimated thin films a deviant molecular orientation, derived from near-edge-X-ray absorption fine structure (NEXAFS) in combination with a lower step height measured by atomic-force-microscopy (AFM), indicates a different behaviour of the flexible terminal hexyl chains during growth in a liquid surrounding. Furthermore, a structural degradation over time is observed which is caused by residual solvent molecules that are incorporated during the transfer procedure.